Učinkovitost serijskega mavčenja, uporabe botulinskega toksina in korekcijskih ortoz za gleženj in stopalo pri skupini otrok s cerebralno paralizo - Jemec, Irena (Rehabilitacija (Ljubljana), 2013)
Background: Because children with cerebral palsy (CP) walk frequently in a typical pattern of toe-walking, they often develop limited range of motion (ROM) in the ankle (limited dorsal flexion). One of the options for improving flexibility is serial casting. We wanted to know whether the serial casting in children with CP who have limited flexibility in the ankle or walk on tiptoes improves flexibility in the ankle. We also wanted to know how the improved flexibility of the ankle influences the gait pattern and how long do the children retain the improved flexibility in the ankle. Methods: The study included children with CP who were able to walk without aids. We collected data on age and diagnosis, assessed movement, spasticity and measured the ROM of the ankles with the knee flexed and extended. In the case of notably increased muscle tone, the children received botulinum toxin into the soleus and gastocnemius muscles. After casting, the children were referred to physiotherapy. The casts were changed weekly; based on the results of ankle ROM we decided whether to continue or end the program. The criterion for the completion of the program was improved flexibility in the ankle in the sense of reaching either the middle position between dorsal and plantar flexion or up to 10° of dorsal flexion. Results: We included 14 children. Due to high muscle tone five children received botulinum toxin. Clinical gait analysis showed an improved gait pattern (in the phase of support, the foot was in full contact). After six months, seven children retained these results and six children started to walk on toes but to a less pronounced extent than before serial casting. The ROM of the ankles was statistically significantly larger after the serial casting program (p < 0.01) and even though it slightly decreased afterwards, it remained improved compared to baseline at the follow-up after six months (p < 0.01). Conclusion: Serial casting in children with CP significantly improves ankle flexibility in the direction of dorsal flexion. The ROM remains statistically significantly improved even six months after the completion of the program.
Keywords: Cerebral palsy; cerebralna paraliza; Child; Contracture; Efficiency; gleženj; kontrakture; otroci; serial casting; serijsko mavčenje; učinkovitost